Growth, morphological, metabolic and photosynthetic responses of clones of eucalyptus to glyphosate - Cerveira Junior, Wilson Roberto [UNESP]; Costa, Yanna Karoline Santos da [UNESP]; Carbonari, Caio Antonio [UNESP]; Duke, Stephen Oscar; Alves, Pedro Luis da Costa Aguiar [UNESP]; Carvalho, Leonardo Bianco de [UNESP] (Elsevier, 2020)
We hypothesized that eucalyptus has clone-dependent responses to glyphosate, and such differential responses might be associated with morphological, metabolic and/or photosynthetic changes. Experiments were carried out under controlled conditions of temperature, photoperiod and nutrition, focusing on evaluating the response of Eucalyptus × urograndis clones (GG100 and I144) to increasing doses of glyphosate (0–1440 g ha−1 acid equivalent – AE) and to test whether a differential plant response would be associated to alterations in leaf morphology, plant and herbicide metabolism and photosynthesis. There was a significant reduction of plant height, stem diameter, number of leaves, leaf area and shoot dry mass caused by low doses of glyphosate (≤180 g AE ha−1, while a strong plant growth reduction (~60%) was caused by glyphosate field doses (≥720 g AE ha−1), in both clones. The GG100 clone was more susceptible to glyphosate field doses, while the I144 clone was more susceptible to glyphosate low doses. The stomatal index increased by 31% and the nervure thickness was reduced by 17% at 30 days after application of glyphosate at 180 g AE ha−1 (DAA) in the GG100 clone. Traces of glyphosate (<28 g mg−1 of dry mass) were found in leaf tissues of both clones at 1 DAA. Shikimic acid accumulated earlier (after 1 DAA) and in greater amounts (90%) in the I144 clone. Aminomethylphosphonic acid (AMPA) was not detected in either treated clone. The CO2 assimilation rate, transpiration rate and stomatal conductance were reduced earlier (after 1 DAA) and more intensely (65%) in the I144 clone. The clone-dependent response is apparently associated with changes in plant metabolism related to glyphosate mode of action and gas exchange response differences between the clones.
Keywords: Dose-response; Eucalyptus urograndis; Herbicide; N-(phosphonomethyl)-glycine; Plant metabolism; Plant physiology